Creating gradients of amyloid fibrils from the liquid–liquid interface. Issue 42 (10th October 2019) - Smith, Kathleen Beth; Fernandez-Rodriguez, Miguel Ángel; Isa, Lucio; Mezzenga, Raffaele
Abstract : We report a method to deposit amyloid fibrils on a substrate creating gradients in orientation and coverage on demand. Abstract : We report a method to deposit amyloid fibrils on a substrate creating gradients in orientation and coverage on demand. For this purpose, we adapt a colloidal self-assembly method at liquid–liquid interfaces to deposit amyloid fibrils on a substrate from the water–hexane interface, while simultaneously compressing it. The amyloid fibril layers orient perpendicularly to the compression, ranging from isotropic to nematic distributions. We furthermore observe reproducible transitions from a monolayer to a bilayer and from a bilayer to multilayers with increasing surface pressures. The creation of each new layer is accompanied by a systematic drop in the structural order of the system, which is however regained upon further compression. This method shows great potential for overcoming the thin-film engineering challenges associated with the manipulation of sticky amyloid fibrils, and allows their ex situ visualisation under compression at the fluid–fluid interface, a situation relevant to understand the propagation of amyloid-related diseases, their functional role in biological systems, and their potential for technological applications.